Mechanical performance and thermal stability of hardened Portland cement-recycled sludge pastes containing MnFe2O4 nanoparticles - O. A. Mohamed; S. I. El-dek; S. M. A. El-Gamal (Scientific Reports, 2023)
Abstract This study focused on investigating the possibility of using different ratios (5, 10, 15 mass%) of recycled alum sludge (RAS) as partial replacement of ordinary Portland cement (OPC), to contribute to solving the problems encountered by cement production as well as stockpiling of large quantities of water-treated sludge waste. MnFe2O4 spinel nanoparticles (NMFs) were used to elaborate the mechanical characteristics and durability of different OPC-RAS blends. The outcomes of compressive strength, bulk density, water absorption, and stability against firing tests fastened the suitability of utilization of RAS waste for replacing OPC (maximum limit 10%). The inclusion of different doses of NMFs nanoparticles (0.5, 1 and 2 mass %) within OPC–RAS pastes, motivates the configuration of hardened nanocomposites with improved physico-mechanical characteristics and stability against firing. Composite made from 90% OPC–10% RAS–0.5% NMFs presented the best characteristics and consider the optimal choice for general construction applications. Thermogravimetric analysis (TGA/DTG), X-ray diffraction analysis (XRD), and scanning electron microscope (SEM) techniques. affirmed the positive impact of NMFs particles, as they demonstrated the formation of enormous phases as ilvaite (CFSH), calcium silicate hydrates (CSHs), MnCSH, Nchwaningite [Mn2 SiO3(OH)2 H2O], [(Mn, Ca) Mn4O9⋅3H2O], calcium aluminosilicate hydrates (CASH), Glaucochroite [(Ca, Mn)2SiO4, and calcium ferrite hydrate (CFH). These hydrates boosted the robustness and degradation resistance of the hardened nanocomposites upon firing.